2021
DOI: 10.1111/cdep.12402
|View full text |Cite
|
Sign up to set email alerts
|

Missing Input: How Imbalanced Distributions of Textbook Problems Affect Mathematics Learning

Abstract: Understanding how environments influence learning requires attending not only to what is present but also to what is absent. In the context of mathematics learning, this means attending not only to problems that children encounter frequently in textbooks but also to ones that appear rarely. We present research in this article showing that students perform surprisingly poorly on seemingly simple fraction and decimal arithmetic problems that are seldom seen in textbooks. Next, we describe imbalanced distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In fact, topics that are not included in textbooks are not usually taught and learned in class (Schmidt et al, 1997). For instance, students are often less proficient in solving certain fraction and decimal mathematical problems, which are rarely found in books (Siegler & Oppenzato, 2021).…”
Section: Textbooks As Part Of the Educational Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, topics that are not included in textbooks are not usually taught and learned in class (Schmidt et al, 1997). For instance, students are often less proficient in solving certain fraction and decimal mathematical problems, which are rarely found in books (Siegler & Oppenzato, 2021).…”
Section: Textbooks As Part Of the Educational Systemmentioning
confidence: 99%
“…In this vein, it is feasible that textbooks from high-performing countries such as Singapore may present more opportunities for students to solve a wider variety of AWPs than those from low-to mid-performing countries. Indeed, lack of experience with some types of problems and/or certain types of schematic representations may hinder children's learning (Siegler & Oppenzato, 2021). There is evidence that textbooks in highperforming countries contain a more diversified and balanced distribution of both additive and multiplicative AWPs across different problem types than textbooks in countries such as the U.S.…”
Section: Textbooks As Part Of the Educational Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparisons within Slovenian mathematics education have shown that teachers in Slovenia lag behind other countries in teaching decimals and fractions, as these topics are covered later (Mullis et al, 2016). Another very important message emerges from recent research on the relationships between textbook content and mathematics learning, focusing on how children learn about rational numbers (i.e., fractions, decimals, percentages) (Siegler & Oppenzato, 2021). It is known from previous research that fraction knowledge in the fifth grade uniquely predicts mathematics achievement five years later in secondary school, even after controlling for socioeconomic status, IQ, reading comprehension and whole number arithmetic knowledge.…”
Section: Introductionmentioning
confidence: 99%